Ethnobotanical Indigenous Knowledge of Tehsil Charhoi, District Kotli, Azad Jammu and Kashmir, Pakistan - Arif, Usman; Bhatti, Khizar Hayat; Ajaib, Muhammad; Wagay, Nasir Aziz; Majeed, Muhammad; Zeb, Jamal; Hameed, Anmol; Kiani, Jawad (Ethnobotany Research and Applications, 2021)
Background: Wild plants are used a lot by the local people of Azad Jammu and Kashmir (AJ&K), Pakistan, for different purposes in daily life. It has been published by various researchers that AJ&K, Pakistan is enriched with wild medicinal flora on the basis of surveys conducted in various parts but some areas are still unexplored. Methods: The present study was conducted from March 2019 to April 2020 and 60 native informants were interviewed from different sites of Tehsil Charhoi. Ethnomedicinal data was collected using a semi-structured questionnaire. Results: In ethno-botanical survey total 100 species of plant were documented that belonging to 52 families and 90 genera. Moraceae was the dominant family in the study area that included 7 species (13.46%). In present ethno-botanical survey total 16 plant parts were utilized for preparation of traditional remedies against for various ailments. The most used plant parts were leaves (28%), followed by roots (18%), fruits (12%), bark, seeds and whole plants (8% each), stems (4%), flowers, wood and latex (3% each), and resin, rhizomes, pods, tubers, gum and aerial parts (1% each). We evidenced a total 18 kinds of preparations curing various diseases with paste (59%) being the most common. The Use Value (UV) index ranged from 0.2 to 0.96. Highest UV was reported for Cuscuta reflexa Roxb. (0.96) whereas lowest UV was reported for Rhamnus triquetra (Wall) Brandis. The Relative Frequency of Citation (RFC) values ranged 0.03 to 0.55. The highest RFC value was obtained for Ficus benghalensis L. (0.55) while Gloriosa superba L. (0.03) had the lowest value. The Informant Consensus Factor (ICF) values ranged 0.21 to 0.68. Diseases were classified into 17 different categories. The high ICF value recorded for jaundice and hepatitis whereas low ICF value for cardiac problems. The highest Fidelity Level (FL) value of Viola canescens Wall (97.1%) was helpful for colds, flu, coughs, constipation, and jaundice. In present study out of 100 medicinal plant species 30 plant species were also utilized for other than medicinal purposes like vegetable, fruit, fodder, fuel, furniture, making agriculture tools, house thatching, walking sticks and handicrafts. In direct matrix ranking of multipurpose species (DMRMS) Dodonaea viscosa (L.) Jacq. ranked first according to information provided by 10 informants. Conclusion: It has been concluded that Tehsil Charhoi, District Kotli, Azad Jammu and Kashmir are rich sources of wild plants used to treat various ailments. There is need to build awareness among local people about the value of medicinal plants and the publication of ethno-botanical information forms the basis for the development of innovative drugs. Keywords: Charhoi, Indigenous, Ethnobotany, Wild, Kotli